Pengaruh Brand Image, Word Of Mouth Dan Celebrity Endorser Terhadap Purchase Decision Produk Facetology - Tessa Kusuma Dewi; Agung Dharmawan Buchdadi; Nofriska Krissanya (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The This research aims to analyze the influence of Brand Image, Word Of Mouth and Celebrity Endorsers on Purchasing Decisions for facetology products. In an era of increasingly fierce business competition, understanding the factors that influence consumer decisions is the key to effective marketing strategies. This research uses quantitative methods with a survey approach to collect data from consumers of Facetology products. The sample used consisted of 200 respondents who were chosen randomly and analyzed using multiple regression. The research results show that Brand Image has a positive and significant influence on purchasing decisions for Facetology products, indicating that a strong brand image can increase consumers' desire to buy the product. Word of Mouth has also been proven to have a positive influence on purchasing decisions, indicating that Word Of Mouth recommendations have a significant impact in influencing consumer decisions. Apart from that, Celebrity Endorsers also provide a significant positive influence, showing that celebrity endorsers can increase product attractiveness and influence consumer Purchasing Decisions. Overall, Brand Image, Word Of Mouth, and Celebrity Endorser together make a significant contribution to Purchasing Decisions for Facetology products. These findings have important implications for the marketing strategies of Facetology and other brands looking to increase their competitiveness in the market. This research suggests that companies should focus more on managing Brand Image, utilizing Word of Mouth, and selecting the right Celebrity Endorser to maximize influence on consumer purchasing decisions.